I started with two polynomial expressions: \(A(x) = 4x^4 - 3x^3 + 2x - 7\) and \(B(x) = 2x^3 + 6x^2 + 1\).
To find the sum of these two polynomials, I combined like terms:
\[ C(x) = A(x) + B(x) = 4x^4 + (-3x^3 + 2x^3) + 6x^2 + (2x) + (-7 + 1). \]
This simplified to:
\[ C(x) = 4x^4 - x^3 + 6x^2 + 2x - 6. \]
The highest degree term in \(C(x)\) is \(4x^4\), which means the degree of this polynomial is 4.
Next, I worked on finding the difference between the two polynomials. For this, I did:
\[ D(x) = A(x) - B(x) = 4x^4 + (-3x^3 - 2x^3) + 6x^2 + (2x) + (-7 - 1). \]
This resulted in:
\[ D(x) = 4x^4 - 5x^3 + 6x^2 + 2x - 8. \]
Then, I moved on to the product of the two polynomials. I found that:
\[ E(x) = A(x) \cdot B(x) \]
would give me a polynomial with a degree of 7, since the degree of \(A(x)\) is 4 and the degree of \(B(x)\) is 3, and I would add those degrees together.
Finally, I looked at the quotient of the two polynomials, \(Q(x) = \frac{A(x)}{B(x)}\). Since the degree of \(A(x)\) is higher than that of \(B(x)\), I used polynomial long division. I found that the result would be of degree 1, as the leading term of \(A(x)\) divided by the leading term of \(B(x)\) gives me an \(x\) term. I can derive the exact expressions for \(E(x)\) and \(Q(x)\) through detailed multiplication and division, but for now, I understand their degrees and how they relate to each other.